PACAP and PAC1R are differentially expressed in motor cortex of amyotrophic lateral sclerosis patients and support survival of iPSC‐derived motor neurons. Issue 4 (20th October 2017) - Bonaventura, Gabriele; Iemmolo, Rosario; D'Amico, Agata G.; La Cognata, Valentina; Costanzo, Erminio; Zappia, Mario; D'Agata, Velia; Conforti, Francesca L.; Aronica, Eleonora; Cavallaro, Sebastiano
Abstract : Amyotrophic lateral sclerosis (ALS) is a fatal and disabling neurodegenerative disease characterized by upper and lower motor neurons depletion. In our previous work, comprehensive genomic profiling of 41 motor cortex samples enabled to discriminate controls from sporadic ALS patients, and segregated these latter into two distinct subgroups (SALS1 and SALS2), each associated with different deregulated genes. In the present study, we focused our attention on two of them, Pituitary Adenylate Cyclase‐Activating Polypeptide ( PACAP ) and its type 1 receptor ( PAC1R ), and validated the results of the transcriptome experiments by quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR), immunohistochemistry and Western blot analysis. To assess the functional role of PACAP and PAC1R in ALS, we developed an in vitro model of human induced pluripotent stem cells (iPSC)‐derived motor neurons and examined the trophic effects of exogenous PACAP following neurodegenerative stimuli. Treatment with 100 nm PACAP was able to effectively rescue iPSC‐derived motor neurons from apoptosis, as shown by cell viability assay and protein dosage of the apoptotic marker (BAX). All together, these data suggest that perturbations in the PACAP‐PAC1R pathway may be involved in ALS pathology and represent a potential drug target to enhance motor neuron viability. Abstract : 1) Two distinct subgroups (SALS1 and SALS2) of sporadic Amyotrophic lateral sclerosis exist and are characterized by different deregulated genes and pathways; 2) Pituitary Adenylate Cyclase‐Activating Polypeptide (PACAP) and its type 1 receptor (PAC1R) are differentially expressed in the two subgroups; 3) PACAP rescues iPSC‐derived motor neurons from apoptosis; and 4) Perturbations in the PACAP‐PAC1R pathway may be involved in ALS pathology.